Comparative In Vitro Study on the Accuracy of Digital versus Conventional Full Arch Implant Impressions. - Amin, Sarah. (2017)
Abstract: Aim & Hypothesis: An accurate implant impression is integral for generating an accurate master cast, which is necessary for the fabrication of an accurately-fitting prosthesis. The aim of this study was to compare two different intra-oral scanners (CEREC Omnicam and 3M True Definition) with each other and with conventional implant impressions in terms of accuracy for a completely edentulous mandibular cast. The hypothesis was that the splinted open tray impressions would be more accurate than digital impressions in cases of complete edentulism. Materials & Methods: A PMMA model representing an edentulous mandible was fabricated using five internal connection implant analogs (Straumann Bone Level RC, Basel, Switzerland). The 3 median implants were parallel to each other, the far left implant had 10 degrees distal angulation and the far right had 15 degrees distal angulation. An impression was taken using polyether to produce a stone master cast to serve as control. Digital impressions (n=10) were taken with two intraoral optical scanners (CEREC Omnicam and 3M True Definition) after connecting polymer scan bodies to the master cast. A splinted open-tray technique was used for the conventional polyether impressions of the master cast (n=10). Master cast and conventional impression casts were digitized with an extra-oral high resolution scanner (Activity 880 scanner; Smart Optics, Bochum, Germany) to obtain digital files. Standard tessellation language (STL) datasets from the three groups of digital and conventional impressions were superimposed with the STL dataset from the master cast to assess the 3-D deviations. Deviations were recorded as root mean square error. To compare the master cast with conventional and digital impressions at the implant-level, Welch's F test was used together with Games-Howell post-hoc test. Results: Group I (conventional impression technique - splinted open tray impression) had a mean value of 167.93 μm (SD 50.37); Group II (OmniCam Digital Impression technique) had a mean value of 46.41μm (SD 7.34); Group III (True Definition Digital Impression Technique) had a mean value of 19.32 μm (SD 2.77). The Kolmogorov-Smirnov test showed no evidence of non- normality. Levene's test showed lack of homogeneity of variances; hence, Welch's F test was used together with the Games-Howell test for post-hoc comparisons. Welch's F test showed a significant difference between the groups (p<0.001). The Games - Howell Test showed statistically significant differences between all three groups (p<0.001). Conclusion: Within the limitations of this in vitro study, full arch digital implant impressions using True Definition scanner and Omnicam were significantly more accurate than the conven- tional impressions with the splinted open-tray technique. Additionally, the digital impressions with the True Definition scanner had significantly less 3-D deviations when compared with the Omnicam.; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Posthodontics.; Advisor: Panos Papaspyridakos.; Committee: Hans-Peter Weber, Khaled El-Rafie, Yukio Kudara, and Matthew Finkelman.; Keyword: Dentistry.